2022
DOI: 10.3390/biology11040605
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Metabolism of Microbial Communities in a Hypersaline Lake along a Geochemical Gradient

Abstract: In the south of western Siberia (Russia), there are many unique and unexplored soda, saline, and freshwater lakes. In this study, the results are presented on microbial diversity, its metabolic potential, and their relation with a set of geochemical parameters for a hypersaline lake ecosystem in the Novosibirsk region (Oblast). The metagenomic approach used in this work allowed us to determine the composition and structure of a floating microbial community, the upper layer of silt, and the strata of bottom sed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Of particular interest is the study of the microbiological characteristics of saline lakes of recreational importance. A comprehensive study of the biogeochemical properties of the bottom sediments of these lakes is one of the current areas of modern microbiology [6][7][8]. In brackish and saline lakes, high mineral content ensures a massive development of microbiota, especially in coastal zones, where the number and species composition of aquatic microorganisms increases dramatically [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest is the study of the microbiological characteristics of saline lakes of recreational importance. A comprehensive study of the biogeochemical properties of the bottom sediments of these lakes is one of the current areas of modern microbiology [6][7][8]. In brackish and saline lakes, high mineral content ensures a massive development of microbiota, especially in coastal zones, where the number and species composition of aquatic microorganisms increases dramatically [4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies [2,6,9,14,[18][19][20][21] show that bottom sediments of saline lakes in Eurasia contain a number of authigenic minerals: calcite, pyrite, rhodochrosite, siderite, barite, etc., which are formed with the direct participation of microorganisms. This process proceeds especially intensively in the upper intervals of bottom sediments in the littoral zone.…”
Section: Introductionmentioning
confidence: 99%
“…Our study found that unclassi ed bacteria, i.e.,Proteobacteria, Bacteroidota, and Actinobacteriota, were the dominant species in all three lakes studied: Aidyn, Brusyanoe, and Rybny Sakryl lakes. These bacterial species are common in majority of the lakes [25,26,27,28,29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…The extreme conditions existent in soda pans and lakes modify their microbial communities, leading to the dominance of extremophiles, with halophiles, alkaliphiles and haloalkaliphiles often dominating these microbiomes (Bryanskaya et al ., 2022). The ability of different microbial taxa to thrive under the alkaline and saline conditions of soda pans stimulate interest among microbiologists about such microbial ecosystems, and elevate the possibility that some of the microorganisms that inhabit these environments have potentially useful applications.…”
Section: Introductionmentioning
confidence: 99%